2010
DOI: 10.1371/journal.pone.0012405
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of DNA Damage Response and Apoptosis Correlate with Jak/Stat and PI3Kinase Response Profiles in Human Acute Myelogenous Leukemia

Abstract: BackgroundSingle cell network profiling (SCNP) utilizing flow cytometry measures alterations in intracellular signaling responses. Here SCNP was used to characterize Acute Myeloid Leukemia (AML) disease subtypes based on survival, DNA damage response and apoptosis pathways.Methodology and Principal FindingsThirty four diagnostic non-M3 AML samples from patients with known clinical outcome were treated with a panel of myeloid growth factors and cytokines, as well as with apoptosis-inducing agents. Analysis of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 70 publications
1
26
0
1
Order By: Relevance
“…However, depending on the type of neoplasm, persistent MRD may not necessarily argue against long-term disease-free survival. In AML, it has been reported that [94][95][96][97] . Conversely, in chronic phase CML, the persistence of a detectable (that is, substantial) population of primitive (presumably pre-malignant) CML stem cells is not predictive of relapse 98 .…”
Section: Evaluation Of Csc Eradicationmentioning
confidence: 99%
“…However, depending on the type of neoplasm, persistent MRD may not necessarily argue against long-term disease-free survival. In AML, it has been reported that [94][95][96][97] . Conversely, in chronic phase CML, the persistence of a detectable (that is, substantial) population of primitive (presumably pre-malignant) CML stem cells is not predictive of relapse 98 .…”
Section: Evaluation Of Csc Eradicationmentioning
confidence: 99%
“…SCNP assays were performed as described previously [24]. Briefly, aliquots of cryopreserved cells were thawed at 37°C, washed, resuspended in RPMI 1640/60% FBS, and mononuclear cells isolated via ficoll density gradient.…”
Section: Methodsmentioning
confidence: 99%
“…It turns out that this information can be catalogued ( Fig. 1), used to create diagnostic predictors at the singlecell level [26][27][28][29]33 and mathematically mined to elucidate cell subsets and responses that correlate to orthologous or surrogate phenotypes. Other correlates include clinical outcomes or drug response 34 , and reconstruction of cellular networks 32,35,36 .…”
Section: Fluorescence-based Flow Cytometrymentioning
confidence: 99%